Deubiquitinating enzyme CYLD mediates pressure overload-induced cardiac maladaptive remodeling and dysfunction via downregulating Nrf2. (July 2015) - Wang, Hui; Lai, Yimu; Mathis, Bryan J.; Wang, Wenjuan; Li, Siying; Qu, Chen; Li, Bin; Shao, Lei; Song, Haibo; Janicki, Joseph S.; Sun, Sao-Cong; Wang, Xing Li; et al.
Abstract: Ubiquitin proteasome system (UPS) consists of ubiquitin, ubiquitin-activating enzymes (E1s), ubiquitin-conjugating enzymes (E2s), ubiquitin ligases (E3s), proteasomes, and deubiquitinating enzymes (DUBs). Ubiquitin, E1s, several E2s, E3s, and proteasomes play an important role in the regulation of cardiac homeostasis and dysfunction; however, less is known about the role of DUBs in the heart. Here, we uncovered a crucial role of cyclindromatosis (CYLD), a DUB, in mediating cardiac maladaptive remodeling and dysfunction. CYLD expression was dramatically upregulated in the cardiomyocytes of hypertrophic and failing human and murine hearts. Knockout of CYLD improved survival rate and alleviated cardiac hypertrophy, fibrosis, apoptosis, oxidative stress, and dysfunction in mice that were subjected to sustained pressure overload induced by transverse aortic constriction. Deep sequencing and gene array analyses revealed that the most dramatically changed genes are those involving in the free radical scavenging pathway and cardiovascular disease, including fos, jun, myc, and nuclear factor erythroid-2 related factor 2 (Nrf2) in the heart. Moreover, knockdown of CYLD enhanced mitogen-activated protein kinase (MAPK) ERK- and p38-mediated expression of c-jun, c-fos, and c-myc, which govern Nrf2 expression in cardiomyocytes. The CYLD deficiency-induced suppression of reactive oxygen species (ROS) formation, death and hypertrophy in cardiomyocytes was blocked by additional knockdown of Nrf2. Taken together, our findings demonstrate for the first time that CYLD mediates cardiac maladaptive remodeling and dysfunction, most likely via enhancing myocardial oxidative stress in response to pressure overload. At the molecular level, CYLD interrupts the ERK- and p38-/AP-1 and c-Myc pathways to suppress Nrf2-operated antioxidative capacity, thereby enhancing oxidative stress in the heart. Highlights: Loss of CYLD suppresses cardiac hypertrophy, fibrosis, cell death, and dysfunction. Loss of CYLD suppresses myocardial oxidative stress. Loss of CYLD upregulates Nrf2 to inhibit ROS formation in cardiomyocytes. Loss of CYLD upregulates Nrf2 to inhibit cardiomyocyte hypertrophy and death.